The Shield and Breaking Bad as televisual fallen-man serial melodramas. Issue 3 (1st October 2019) - Pierson, David
This article argues that the television series The Shield (2002–08) and Breaking Bad (2008–13) are televisual 'fallen-man' serial melodramas. Janet Staiger (2008) coined the term 'fallen-man' to define the male melodramas produced during the American film noir cycle (1945–59). Unlike the classic film noir victim-protagonist, The Shield's Vic Mackey and Breaking Bad's Walter White are not led astray by a femme fatale but rather through their own egos, which interfere with them controlling their morality. As with the filmic fallen-man melodramas, both Vic and Walter make explicit, psychologized choices of action that place them on their immoral pathways. The televisual fallen man melodramas are expressive of social and cultural anxieties confronting middle-class, white males in western societies. Because Vic and Walter perceive themselves as cultural and economic victims, they commit heinous acts against their families, colleagues and others – all in the pursuit of attaining social power and autonomy in a post-9/11 multicultural America.